Rotor Drop Characteristics of Active Magnetic Bearings under Typical Maneuvering Conditions - Liao, Junfei; Wang, Xiaohu (Scientific Journal of Technology, 2026)
To address the critical safety risks of high-speed rotor drop and subsequent rub-impact following the failure of active magnetic bearings (AMBs) in aero-engines, this paper establishes a nonlinear dynamic model for a flexible AMB rotor-protective bearing system that fully couples maneuvering flight loads. The rotor model is constructed based on the Timoshenko beam theory and the finite element method (FEM). By incorporating the Hunt-Crossley nonlinear contact model and the multidimensional maneuvering additional inertial force field, the transient dynamic equations of the system are solved over the entire process using the Newmark-HHT method. Furthermore, the evolutionary laws of the rotor drop impact characteristics under vertical translational overload, rolling maneuvers, and coupled translational-rotational maneuvers are systematically and quantitatively analyzed.